Implementasi Teknologi IoT untuk Monitoring Suhu dan Kelembaban pada Usaha Tani Hortikultura - Agus Bahtiar; Ahmad Faqih; Chulyatunni’mah; Madyant (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Horticultural farming is highly dependent on environmental conditions, particularly temperature and humidity. Unstable weather conditions often cause problems in plant growth, trigger pest and disease outbreaks, and reduce crop yields. Based on these challenges, this community service program aims to implement Internet of Things (IoT) technology as a solution for real-time monitoring of temperature and humidity in horticultural farmland. The program’s partners are farmer groups who have been using manual methods to monitor environmental conditions. This activity was carried out in several stages: needs identification, IoT system design and installation, training for system usage, and post-implementation evaluation. The developed system consists of temperature and humidity sensors, microcontrollers, and a cloud based dashboard connected to a mobile application, allowing farmers to monitor conditions anytime. The system also features automatic notifications when extreme temperature or humidity changes are detected. The results show improvements in monitoring efficiency and farmers' responsiveness to environmental changes. Farmers can make quicker decisions, reducing the risk of crop failure. Additionally, the efficient use of resources such as water and fertilizer has increased, resulting in lower operational costs and higher income. In terms of digital literacy, this program has also contributed to improving technological skills among farmers. With the implementation of IoT technology, this program supports the transformation toward smart farming. It is expected not only to improve productivity but also to enhance the resilience and sustainability of horticultural farming in the future.